Spectroradiometric characteristics of Scots pine and intensity of moose browsing. - Silvennoinen, Raimo; Hämäläinen, Rauno; Nygrén, Kaarlo; Weissenberg, Kim (Silva Fennica, 1991)
The light reflected from the crowns of Scots pine ( L.) clones was measured spectroradiometrically during and after growing season. Standard deviations of the spectra of pine clones showing differences in moose browsing intensity were compared. A new algorithm was developed for predicting the browsing intensity of moose ().Pinus sylvestrisAlces alces